Überlegungen zur Lockerung des Lockdowns - Michael Hüther; Hubertus Bardt (Wirtschaftsdienst, 2020)
Die durch das Coronavirus verursachte Pandemie stellt ein beachtliches gesundheitliches Risiko dar. Zur Bewältigung dieser Krise müssen in erheblichem Umfang wirtschaftliche Ressourcen für das Gesundheitssystem eingesetzt werden. Angesichts der gesundheitlichen Risiken sind die hierfür aufzubringenden Kosten gegenwärtig nicht relevant. Wenn der Lockdown endet, ist jedoch mit erheblichen Anpassungsproblemen und Stockungen auf dem Weg zu einer wieder friktionsfrei arbeits-, risiko- und wissensteiligen Volkswirtschaft zu rechnen. – – The fight against the coronavirus pandemic has led to an insulation of social and economic life and will have considerable economic consequences. Important areas of the industry and service sectors were partially or completely shutdown. A resumption of activity should happen as soon as possible, once the medical pre-conditions have been established and are met. This requires a clear exit strategy and following several steps to return to previous welfare and growth data levels. After securing survival during this crisis via various liquidity lines and bridging loans, the economy's restart requires the relaunch of public infrastructure, especially of schools and kindergartens. To facilitate a coordinated and synchronised restart of complex industrial value chains, we need clear signals on a planned schedule. A tax policy driven departure signal and a demand side focused growth programme could make an important contribution to a new economic dynamic after the crisis.
Keywords: O40; I15; H12; 330